Road to Total Knee Replacement: Utilization of Knee Surgeries Up to Ten Years Before Total Knee Replacement in England and Sweden. Issue 5 (20th December 2022) - Dell'Isola, Andrea; Appleyard, Tom; Yu, Dahai; Hellberg, Clara; Thomas, Geraint; Turkiewicz, Aleksandra; Peat, George; Englund, Martin
Abstract : Objective: To compare the prevalence and timing of knee surgery (including meniscal, ligamentous, synovial, and osteotomy) in the 10 years prior to primary total knee replacement (TKR) between England and Sweden. Methods: This was a population‐based, case–control study within England and southern Sweden using electronic health care databases. Patients underwent primary TKR between 2015 and 2019. Risk‐set sampling showed that general population controls matched 1:1 by age, sex, and practice/municipality. The annual prevalence and prevalence ratio of having at least 1 recorded surgery in each of the 10 years preceding TKR was estimated using Poisson regressions. Results: We included 6, 308 and 47, 010 TKR cases in Sweden and England, respectively. Meniscal surgeries were the most frequent procedure prior to TKR in both countries; prevalence was higher in England across all time points. The prevalence of meniscal surgery increased in both countries in the years approaching TKR, reaching 33.2 (95% confidence interval [95% CI] 31.6–34.9) per 1, 000 persons in England, and 9.83 (95% CI 7.66–12.61) in Sweden. In England, we observed a decrease from 2014 to 2018 in the utilization of this procedure in the 4 years preceding a TKR. The prevalence of all analyzed surgeries was consistently lower in controls. Conclusion: There are comparable trends in the use of knee surgery in the years preceding TKR across England and Sweden. Of note, meniscal surgeries remain common, even within the year prior to TKR, highlighting that these patients may experience low‐value care. Careful consideration of knee surgery in those with late‐stage disease is required.